Transvaginal mesh surgery for pelvic organ prolapse does not affect sexual function at long term follow up. (September 2019) - Morselli, Simone; Li Marzi, Vincenzo; Verrienti, Pierangelo; Serati, Maurizio; Di Camillo, Matteo; Tosto, Aldo; Milanesi, Martina; Serni, Sergio
Abstract: Objective: Pelvic Organ Prolapse (POP) may impair sexual health. Though sexual dysfunction in women with POP is associated with reduced sexual arousal and dyspareunia, sexual outcomes have not been fully investigated. Transvaginal mesh repair (TVMR) is a POP therapeutic option, but is debated as a possible cause of worsening in sexual function. Aim of this study is to evaluate pre- and post-operative sexual outcomes in women undergone to TVMR. Study Design: Data coming from sexually active women submitted to TVMR for POP with commercial mesh kits (device whose production has been suspended) were prospectively collected from 2012 to 2016 in a tertiary referral center. POP was measured according to the POP-Q classification. Patients' characteristics, operative and post-operative data were collected. Follow-up was carried out at month 1, 6, 12 and then yearly. Sexual function was measured through FSFI (Female Sexual Function Index) questionnaire. Minimum follow up was 12 months. FSFI score was assessed in these women before and after TVMR. A sub-analysis according to mesh kit used was made. Results: From 2012 to 2016, 155 women underwent TVMR active for stage III or higher POP and 56 (36.6%) were sexually active, while 52 (92.9%) had adequate follow-up. Median age was 62 years (IQR 56–66), median BMI was 24, 7 kg/m2 (IQR 22, 3–28, 9) and median parity was 2 (IQR 1–2). All patients presented anterior compartment POP and 14 (269%) had previous POP surgery. Urodynamic SUI was present in 13 (250%) patients. Commercial mesh kits used were Prolift© in 19 patients (36.5%) and Elevate© in 33 (63.5%). Median follow up was 42 months (IQR 22–59). Globally, FSFI was unaltered from TVMR at 12 months and at last follow up (p = 0.856). In detail, even if dyspareunia was reported in 1 patient, pain sub score was stable at long term follow up after TVMR (p = 0.124). Globally, there were 8 (15.4%) perioperative complications, none exceeding Clavien 2. At late follow up here was 1 (1.9%) mesh vaginal erosion occurred and there were 4 (7.7%) de novo stress urinary incontinence. Preoperative characteristics, surgical complications and outcomes were similar between mesh kits (p > 0.05). Conclusion: In our experience, global sexual function doesn't seem to be affected by TVMR when performed by expert surgeons. Despite being a confounding factor, lost at follow up rate was low, thus affecting only in a mild way surgical outcomes. Also ageing might be a confounding factor during follow up to establish real mesh impact on sexual function. Dyspareunia was a rare complication in patients during follow-up and pain was not a major complaint.